2009
DOI: 10.1097/nen.0b013e3181b40217
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Rats Exposed to Dichloroacetate

Abstract: The use of dichloroacetate (DCA) for treating patients with mitochondrial diseases is limited by the induction of peripheral neuropathy. The mechanisms of DCA-induced neuropathy are not known. Oral DCA treatment (50–500 mg/kg/day for up to 16 weeks) induced tactile allodynia in both juvenile and adult rats; concurrent thermal hypoalgesia developed at higher doses. Both juvenile and adult rats treated with DCA developed nerve conduction slowing that was more pronounced in adult rats. No overt axonal or glial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…DCA treatment for 8 weeks induced mild weight loss (control ϭ 282 Ϯ 5 versus DCA ϭ 259 Ϯ 3 g; mean Ϯ S.E.M., p Ͻ 0.001 by unpaired t test) and peripheral neuropathy, as illustrated by slowing of motor nerve conduction velocity (control ϭ 50.3 Ϯ 1.9 versus DCA ϭ 42.5 Ϯ 1.1 m/s; p Ͻ 0.01) and paw thermal hypoalgesia (control ϭ 10.35 Ϯ 0.62 versus DCA ϭ 13.34 Ϯ 0.72 s; p Ͻ 0.001), as has been reported for rats treated with a similar dose of DCA (Calcutt et al, 2009).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…DCA treatment for 8 weeks induced mild weight loss (control ϭ 282 Ϯ 5 versus DCA ϭ 259 Ϯ 3 g; mean Ϯ S.E.M., p Ͻ 0.001 by unpaired t test) and peripheral neuropathy, as illustrated by slowing of motor nerve conduction velocity (control ϭ 50.3 Ϯ 1.9 versus DCA ϭ 42.5 Ϯ 1.1 m/s; p Ͻ 0.01) and paw thermal hypoalgesia (control ϭ 10.35 Ϯ 0.62 versus DCA ϭ 13.34 Ϯ 0.72 s; p Ͻ 0.001), as has been reported for rats treated with a similar dose of DCA (Calcutt et al, 2009).…”
Section: Resultssupporting
confidence: 54%
“…ALDH1A1 is a cytosolic and inducible isoform of the aldehyde dehydrogenase family that catalyzes the oxidation of medium-chain aliphatic aldehydes, including 4-hydroxynonenal and malondialdehyde (Alnouti and Klaassen, 2008). This is noteworthy because elevated levels of these indices of lipid peroxidation have been found in the sciatic nerves of rats treated with the same dose of DCA as used in the present study (Calcutt et al, 2009). Furthermore, increased production of reactive oxygen species and lipid peroxidation have been demonstrated in the livers of mice treated with high doses of DCA (Larson and Bull, 1992;Hassoun et al, 2010).…”
Section: Mitochondrion As a Site Of Dichloroacetate Biotransformation 91mentioning
confidence: 49%
See 1 more Smart Citation
“…This study therefore has demonstrated that by increasing the metabolic flexibility of the hyperthyroid heart, the response to increased levels of thyroid hormone is altered and cardiac hypertrophy is reduced. The side effects associated with DCA treatment, ie, pain, numbness, and peripheral neuropathy, 45,46 prevent DCA from being a viable treatment for hyperthyroidism; however, our data suggest that alternative metabolic interventions may relieve some of the more serious symptoms associated with this disease and therefore warrant further investigation.…”
Section: Effects Of Dichloroacetic Acid Treatment On the Hyperthyroidmentioning
confidence: 61%
“…DCA neuropathy was induced by daily injection (1.0 g/kg i.p.) throughout the study (43,81). Local exposure to gp120 (product 1021, ImmunoDX) was used to model HIV neuropathy (44).…”
Section: Methodsmentioning
confidence: 99%